2011
DOI: 10.1299/kikaic.77.1143
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ordered Gold Nano Dot Array by Nano Plastic Forming and Self-Assembly

Abstract: A new fabrication method of ordered metal nano dot array is developed by using coating, nano plastic forming (NPF) and self-assembly due to annealing. In this study, the combination of these processes is studied to produce uniformly-sized and ordered gold nano dot array on a quarts glass substrate experimentally. The results reveal that patterning of lattice grooves on the gold-coated substrate with the NPF is effective to obtain the ordered gold nano dot array. In the proposed fabrication process, the size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…84 Their approach is using NPF combined with the thermal dewetting process. [84][85][86] This demonstrated low-cost yet high-throughput plasmonic. NPLA structure has been successfully fabricated without resist employment or deposition of the adhesion layer.…”
Section: Fabrication Of Nanopillar Arrays (Npla)mentioning
confidence: 98%
See 1 more Smart Citation
“…84 Their approach is using NPF combined with the thermal dewetting process. [84][85][86] This demonstrated low-cost yet high-throughput plasmonic. NPLA structure has been successfully fabricated without resist employment or deposition of the adhesion layer.…”
Section: Fabrication Of Nanopillar Arrays (Npla)mentioning
confidence: 98%
“…However, the report of fabrication of nanopillar by this technique nowadays is still rarely found except for the fabrication of nanodots. 86,91 Figure 5 shows the comparison of schemes of EBL, NIL, and NPF techniques to produce nanopillars.…”
Section: Fabrication Of Nanopillar Arrays (Npla)mentioning
confidence: 99%
“…Figure 2 shows the NPF equipment. Details of the equipment are explained in previous papers [19][20][21]. A single crystal diamond knife-edge tool shown in figure 2 was used for the experiment.…”
Section: Experimental Processesmentioning
confidence: 99%
“…An alternative simple method for the fabrication of nanodot arrays is based on the dewetting process of thin metal films on a substrate. Authors have developed a new method to fabricate twodimensional (2D) nanodot arrays through the combination of nano-plastic forming (NPF) and thermal dewetting [19,20]. In this method, various process conditions including pitch setting, annealing time and annealing temperature are controlled to tune the size and morphology of the nanodot array.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have proposed a new fabrication method of the metal nano-dots array by a combination of the nano plastic forming (NPF) technique which is direct imprinting method and the self-assembly of thin film during high-temperature annealing. With the proposed method, we have already demonstrated that well-ordered gold (Au) nano-dots array can be fabricated efficiently [6]. Also, the size and interparticle distance can be controlled by adjusting the condition of the NPF and the annealing.…”
Section: Introductionmentioning
confidence: 99%